2004
DOI: 10.1210/en.2004-0395
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Captured Single Digoxigenin-Labeled Neurons of Gonadotropin-Releasing Hormone Types Reveal a Novel G Protein-Coupled Receptor (Gpr54) during Maturation in Cichlid Fish

Abstract: GPR54 is a novel G protein-coupled receptor speculated to be essential for sexual development. However, its role in the regulation of GnRH types is unknown. To address this issue, we cloned GPR54 from the brain of a cichlid fish (tilapia Oreochromis niloticus) and determined its expression in immature and mature males using our newly developed technique: laser-captured microdissection of single digoxigenin-labeled GnRH neurons coupled with real-time quantitative PCR. The tilapia GPR54 cDNA contains an open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
171
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(194 citation statements)
references
References 12 publications
17
171
0
6
Order By: Relevance
“…If kisspeptin neurons communicate directly with GnRH neurons, one would expect GnRH neurons to express GPR54. Parhar et al (2004) isolated GnRH neurons from the cichlid fish Oreochromis niloticus by laser capture microscopy and identified GPR54 mRNA transcripts in these cells by realtime quantitative RT-PCR. They found that approximately 50% of GnRH neurons in these animals coexpress GPR54.…”
Section: How Kiss1 Got Its Namementioning
confidence: 99%
“…If kisspeptin neurons communicate directly with GnRH neurons, one would expect GnRH neurons to express GPR54. Parhar et al (2004) isolated GnRH neurons from the cichlid fish Oreochromis niloticus by laser capture microscopy and identified GPR54 mRNA transcripts in these cells by realtime quantitative RT-PCR. They found that approximately 50% of GnRH neurons in these animals coexpress GPR54.…”
Section: How Kiss1 Got Its Namementioning
confidence: 99%
“…Kisspeptins are termed kisspeptin 10, 13, 14, and K54 according to the number of amino acids in length, and the decapeptide kisspeptin 10, which is shared by all the members of kisspeptin family, is required for the biological activity (Kotani et al 2001). Gonadotropinreleasing hormone (GnRH) neurons have been shown to express GPR54 receptor (Parhar et al 2004), through which kisspeptins activate GnRH secretion (Messager et al 2005). In a recent study (Beale et al 2014), kisspeptin knockdown in the arcuate nucleus (ARC) has been reported to result in a decrease in luteinizing hormone (LH) pulse frequency, which suggests that maintenance of ARC-kisspeptin levels is essential for normal pulsatile LH release and estrous cyclicity.…”
Section: Introductionmentioning
confidence: 99%
“…In tilapia brain, GPR54 co-localizes with neurons expressing GnRH1, GnRH2 and GnRH3, suggesting an involvement of kisspeptin system in the regulation of GnRH system expression as in mammals (Parhar et al, 2004). Higher levels of GPR54 expression in the brain have been discovered in mature than in immature animals, thus to hypothesize a link between gonadal development and encephalic GPR54 expression (Parhar et al, 2004). Similarly to mammals, kiss1 gene has been identified in two distinct neuronal populations that exhibited a differential response to steroid milieu (Kanda et al, 2008).…”
Section: Kisspeptin Systemmentioning
confidence: 97%